The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/agj2.20790
|View full text |Cite
|
Sign up to set email alerts
|

Integrating multiple inputs for soft red and white winter wheat

Abstract: Michigan winter wheat (Triticum aestivum L.) growers continue to adopt intensive management strategies. However, instead of broadscale implementation of an entire collection of inputs simultaneously, practitioners question which inputs may better contribute to improved production. Studies evaluated soft winter wheat plant growth, grain yield, and expected economic net return for multiple agronomic and nutrient inputsacross varying production intensities. Field trials established in Richville and Lansing, MI, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…The studies above provided insights into individual management practices to improve wheat grain yield. Others attempted to quantify wheat yield response to intensified management, combining the prophylactic use of a number of inputs to minimize yield gaps ( Mohamed et al, 1990 ; Jaenisch et al, 2019 ; Quinn and Steinke, 2019 ; de Oliveira Silva et al, 2020b ; Herrera et al, 2020 ; Roth et al, 2021 ; Steinke et al, 2021 ). However, with few exceptions ( de Oliveira Silva et al, 2020b , 2021 ), these efforts mostly overlooked the mechanisms behind the yield responses and simply quantified the magnitude of yield improvements.…”
Section: Introductionmentioning
confidence: 99%
“…The studies above provided insights into individual management practices to improve wheat grain yield. Others attempted to quantify wheat yield response to intensified management, combining the prophylactic use of a number of inputs to minimize yield gaps ( Mohamed et al, 1990 ; Jaenisch et al, 2019 ; Quinn and Steinke, 2019 ; de Oliveira Silva et al, 2020b ; Herrera et al, 2020 ; Roth et al, 2021 ; Steinke et al, 2021 ). However, with few exceptions ( de Oliveira Silva et al, 2020b , 2021 ), these efforts mostly overlooked the mechanisms behind the yield responses and simply quantified the magnitude of yield improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent research on S fertilization of wheat is lacking, one study in Kansas found that the addition of S fertilizer increased winter wheat's grain yield by 0.3 Mg ha −1 across 2 yr within a no‐tillage system (Jaenisch et al., 2019). In Michigan, starter fertilizer containing N, P, S, and Zn increased the yield of soft red and white winter wheat compared with an untreated control at all four site‐years of the study (Steinke et al., 2021). However, the individual effects of N, P, S, and Zn could not be separated, as the starter fertilizer contained all four elements.…”
Section: Introductionmentioning
confidence: 96%